Contribution of translocated greater sage‐grouse to population vital rates. Issue 6 (18th April 2017) - Duvuvuei, Orrin V.; Gruber‐Hadden, Natasha W.; Messmer, Terry A.; Guttery, Michael R.; Maxfield, Brian D.
ABSTRACT: Range‐wide declines of greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse) populations have been attributed to long‐term habitat alteration and fragmentation. In areas that still exhibit suitable habitats and where population declines have been attributed to other threats (e.g., invasive predators), managers have successfully used translocations to augment declining wildlife populations. However, translocations to augment sage‐grouse populations have had limited success and the relative contribution of translocated sage‐grouse to declining populations is not well understood. From 2009 to 2012 we studied the vital rates of 34 resident (21 yearlings and 13 adults) and 60 translocated radio‐marked female sage‐grouse (30 yearlings and 30 adults) on Anthro Mountain in northeastern Utah, USA to determine the relative contributions of each group to population productivity. We used the encounter histories of the monitored sage‐grouse to construct nest survival models for program MARK to assess the impacts of age and residency status on annual survival and overall reproductive success in the population. Annual survival was not affected by age or residency status and averaged 0.40 (95% CI = 0.31–0.50). The yearling newly translocated females (translocated females during their first yr in the release area) exhibited the lowest nest initiation rates (0.50, 95% CI = 0.30–0.69), whereas adult resident and previously translocated (translocated females that survived ≥1 yr in the release area) females had the highest nest initiation (0.96, 95% CI = 0.88–0.99). Overall nest success (0.43, 95% CI = 0.30–0.55) and brood success (0.55, 95% CI = 0.41–0.69) were not affected by residency status or age. The adult resident and previously translocated females exhibited the highest overall reproductive success (0.22, 95% CI = 0.14–0.31) followed by resident yearling females (0.20, 95% CI = 0.12–0.29), and newly translocated adult females (0.18, 95% CI = 0.10–0.27). Newly translocated yearling females had the lowest overall reproductive success (0.12, 95% CI = 0.05–0.18). Survival of adult females is a major factor influencing sage‐grouse population stability. Although adult and yearling newly translocated females had similar survival rates, adult translocated females were more likely to raise a brood in their first year in the release area. Thus, managers should consider translocating a higher ratio of adult to yearling females in future translocation efforts to see a more immediate effect on population growth in the release area. However, because of the low vitals rates recorded in our study, managers should identify and mitigate the limiting factors affecting the resident population prior to implementing a translocation to augment declining populations. © 2017 The Wildlife Society. Abstract : We investigated the relative contribution of translocated greater sage‐grouse to population growth in the release area. Translocated sage‐grouse adapted to the release area and experienced survival and reproductive success similar to the residents, but vital rates remained low, indicating that managers should address limiting factors prior to the augmentation.